2003
DOI: 10.1186/cc2393
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction The objective of the present study was to evaluate the use of a single lumen 16 G central venous catheter for the drainage of uncomplicated pleural effusions in intensive care unit patients. Methods A prospective observational study was performed in two intensive care units of university-affiliated hospitals. The study involved 10 intensive care unit patients with non-loculated large effusions. A 16 G central venous catheter was inserted at the bedside with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The 19 included studies are summarized in Table 1 ; the authors of three studies provided additional information [ 4 , 31 , 32 ]. Four studies measured physiological effects of pleural drainage [ 31 , 33 - 35 ]; seven studies assessed the safety of thoracentesis [ 36 - 42 ]; and three studies assessed the accuracy of ultrasonographic prediction of pleural effusion size [ 43 - 45 ]. Four studies employed real-time ultrasound guidance [ 32 - 34 , 46 ] and eight studies employed ultrasound to mark the puncture site for thoracentesis [ 36 , 38 - 41 , 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 19 included studies are summarized in Table 1 ; the authors of three studies provided additional information [ 4 , 31 , 32 ]. Four studies measured physiological effects of pleural drainage [ 31 , 33 - 35 ]; seven studies assessed the safety of thoracentesis [ 36 - 42 ]; and three studies assessed the accuracy of ultrasonographic prediction of pleural effusion size [ 43 - 45 ]. Four studies employed real-time ultrasound guidance [ 32 - 34 , 46 ] and eight studies employed ultrasound to mark the puncture site for thoracentesis [ 36 , 38 - 41 , 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of enrolled patients ranged from 35 to 74 years. Of 494 patients in six studies reporting the type of effusion [ 4 , 31 , 34 , 40 , 42 , 46 ], 42% were classified as exudative, 55% transudative (as defined in each study), and the remaining 3% had indeterminate biochemical findings.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the indwelling time was similar in successfully treated patients in both groups. If catheter obstruction does occur, it can be cleared by simply rinsing with physiological saline or, even more effectively, by using the guide wire supplied with the catheter (Shang and Lou, 2001;Singh et al, 2003). In contrast, obstructed chest tubes are difficult to clear, and patients can be treated only by replacing the catheter/tube or by repeated puncture tapping.…”
Section: Discussionmentioning
confidence: 99%
“…Although the drainage speed of a CVC is slower than that of a chest tube, we found that a CVC was still able to drain >1 000 ml of effusion fluid per hour in large hemothorax cases. Singh et al (2003) used CVCs to drain pleural effusions in 15 patients and recorded a mean drainage volume of (454±241) ml in the first hour after catheterization, substantially higher than 200 ml/h. This suggests that use of an unobstructed CVC would not hinder the identification of progressive hemothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a central venous catheter inserted using a Seldinger technique may be efficacious, well tolerated and with minimal complications in draining uncomplicated large PEs [57]. …”
Section: Management Of Pes In Critically Ill Patientsmentioning
confidence: 99%